The effect of bending and twisting on the stiffness and strength of the 3.5 SOP implant - Ness, M. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
Locking plates are becoming increasingly popular in veterinary orthopaedics. The SOP is a novel locking plate system, which can be contoured with 6° of freedom and which utilises standard bone screws. The purpose of this work was to investigate the mechanical consequences of contouring the 3.5 SOP plate to support the formulation of clinical guidelines. The implants were loaded in four point bending using an industry standard protocol. The uncontoured SOP was found to be significantly stiffer and stronger than the uncontoured 3.5 DCP. Bending, and to a lesser extent, twisting, diminished the SOP’s stiffness and strength but the contoured SOP remained at least as stiff and strong as the untouched DCP.
Keywords: SOP; stiffness; strength; contouring; locking plate